Venture performance in Malaysia : personal initiative, human capital, and areas of founding entrepreneurs as critical success factors - Sambasivan, Murali; Lim, Li Yen; Che Rose, Raduan; Abdul, Mohani (Routledge, 2010)
This paper investigates the impact of factors such as personal initiative (PI), human capital, and competencies of founding entrepreneurs on venture growth. Malaysian entrepreneurs, who have taken their firms to the growth stage, have been used as respondents in this study. The factor PI is relatively new to entrepreneurial research. Consistent with the theory, it is found that firms managed by high PI entrepreneurs achieve higher growth. In this study, competencies of founding entrepreneurs have been found to have a significant impact on venture growth.